Continuing conflict, continuing displacement in southern Afghanistan - Amiri, R (Refugee Studies Centre, University of Oxford, 2014)
With fighting and insecurity likely to remain dominant features of Afghanistan’s landscape in the immediate future, displacement will continue to ebb and flow